2015
DOI: 10.1007/s10534-015-9873-5
|View full text |Cite
|
Sign up to set email alerts
|

Deferasirox-TAT(47–57) peptide conjugate as a water soluble, bifunctional iron chelator with potential use in neuromedicine

Abstract: Deferasirox (DFX), an orally active and clinically approved iron chelator, is being used extensively for the treatment of iron overload. However, its water insolubility makes it cumbersome for practical use. In addition to this, the low efficacy of DFX to remove brain iron prompted us to synthesize and evaluate a DFX-TAT(47-57) peptide conjugate for its iron chelation properties and permeability across RBE4 cell line, an in vitro model of the blood-brain barrier. The water-soluble conjugate was able to remove … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
2
8
0
2
Order By: Relevance
“…Goswami et al were synthesized the deferasirox-TAT(47-57) peptide conjugate to obtain water soluble alternatives of deferasirox, and also better efficacy to chelate brain iron. It was reported that solubility of deferasirox was increased from <1 mg/mL to >10 mg/mL [27]. In our study, maximum solubility increase was obtained with 10% SLS at pH 1.2 (from 0.9 µg/mL to 333.7 µg/mL), and with 5% Pluronic F127 at pH 6.8 (from 46.8 µg/mL to 334.2 µg/mL).…”
Section: Solubility Studysupporting
confidence: 56%
“…Goswami et al were synthesized the deferasirox-TAT(47-57) peptide conjugate to obtain water soluble alternatives of deferasirox, and also better efficacy to chelate brain iron. It was reported that solubility of deferasirox was increased from <1 mg/mL to >10 mg/mL [27]. In our study, maximum solubility increase was obtained with 10% SLS at pH 1.2 (from 0.9 µg/mL to 333.7 µg/mL), and with 5% Pluronic F127 at pH 6.8 (from 46.8 µg/mL to 334.2 µg/mL).…”
Section: Solubility Studysupporting
confidence: 56%
“…Here we report that the selected MPPs were synthesized and linked to DFO by means of succinylation following the synthetic strategy established in our previous studies [ 10 , 15 ], although most steps were carried out at 60°C using conventional heating. After purification and characterization, the four mitochondria-targeted DFO conjugates (mtDFO, Fig 1 ) had their iron binding and antioxidant (against an iron-dependent oxidation model) properties studied.…”
Section: Introductionmentioning
confidence: 99%
“…Cationic cell-penetrating peptides (CPPs) can facilitate the internalization of attached macromolecules and even nano-carriers (e.g., polymers, liposomes) by various cells via independent transporters and receptor-mediated endocytosis [ 21 , 22 ]. A number of CPPs including trans-activating transcriptional activator (TAT), angiopep, penetratin, rabies virus glycoprotein (RVG), prion peptide, and SynB have already been demonstrated the ability of improving drug delivery across the BBB [ 23 , 24 ]. Peptide Tat (YGRKKRRQRRR), derived from TAT protein, can increase the permeability of brain endothelial cells by inhibiting occludin expression and cleaving occludin via matrix metalloproteinase-9 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%